Penerapan model pembelajaran OIDDE untuk meningkatkan keterampilan pembelajaran berbasis karakter pada guru pendidikan dasar dan menengah - Miftachul Hudha, Atok; Sukarsono, Sukarsono; Handayani, Ning Rahayu (University of Islam Malang, 2021)
The application of character values through classroom learning has not been maximal because teachers have difficulty choosing the right learning model. The OIDDE (Orientation, Identify, Discussion, Decision, and Engage in Behavior) learning model is appropriate to implement. This article aims to describe the implementation of teacher assistance activities in developing character values through learning by applying the OIDDE learning model. The subjects of the service were 12 teachers at SD / MI levels, 12 teachers from SMP / MTs, and 15 teachers at SMA / SMK / MA levels from 39 schools in Batu City, East Java. The activity was carried out for 6 months using the Forum Group Discussion (FGD) method, workshops, hands-on practice, outreach, and evaluation. The evaluation of community service is carried out thoroughly, from the process to the output, especially the seriousness of the teacher in participating in the activities to the skills in applying the model. The results of the process evaluation show that, the service activity is carried out well, the average attendance is 85%, and as many as 100% of the teachers become the Master Teacher model. OIDDE learning, and has the right to provide tutors with OIDDE learning models.